The Problems of Business Competition Supervisory Commission’s Authority of Core-Plasma Partnership Agreements - Gultom, Elisatris; Kamillah, Ananda Syifa (Simbur Cahaya, 2023)
One of the government's efforts to improve the ability of Micro, Small, and Medium Enterprises (“MSMEs”) to conduct business activities is to execute a partnership system between Large Enterprises and MSMEs. In practice, violations are still found in the implementation of partnerships between Large Enterprises and MSMEs, the appropriate supervision is required from the relevant institutions. This paper examined the legal basis of the Business Competition Supervisory Commission (“KPPU”) in supervising the implementation of partnerships between Large Enterprises and MSMEs as well as the form of supervision conducted by KPPU on the implementation of partnerships. The research used a normative juridical by using secondary data sources. The typology of research used descriptive-analytical, which describes the authorities of KPPU in supervising business competition in Indonesia in terms of the implementation of partnerships comprehensively. This study has resulted, even though Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition does not state KPPU’s authority to supervise partnerships, though concerns to several related laws and regulations such as Law Number 20 of 2008 concerning MSMEs in conjunction with Government Regulation Number 7 of 2021 concerning the Ease, Protection, and Empowerment of Cooperatives and MSMEs, it is found that provisions authorize KPPU to supervise partnerships. The form of supervision over implementing partnerships conducted by KPPU includes providing consultations, evaluations, suggestions, and considerations related to government policies, harmonization of policies, and law enforcement. Furthermore,  examining of alleged violations of the oil palm plantations of core plasma partnership between PT STP and Koperasi THB marks the KPPU's authority in partnerships law enforcement.